PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 108 PEKANBARU - Hartini, Desi; Alim, Jesi Alexander; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstarck : This was a classroom research (PTK) which has two cycles which was conducted on 10-27 March 2015. The data shown the either learning process increased. The basic score of daily examination as 13,29% which 18 students passed and 12 students failed. The ending of daily examination was 60% and the average was 73,83% on the passing grade. The second daily examination also increased from basic score as 5,65% which 26 students passed and 4 students failed. The ending of second daily examination was 86,67% and the average was 78,00. Based on the explanation above it can be concluded that the implementation of student team achievement division (STAD) increased students’ achievement the result of science studies of students IV grade of State Elementary School 108 Pekanbaru.Keywords : Cooperatif Student Achievement Team Division (STAD), Students Achievement The Result Of Science Studies